CXCL12 chemokine and GABA neurotransmitter systems crosstalk and their putative roles - Guyon, Alice (Frontiers in Cellular Neuroscience, 2014)
Since CXCL12 and its receptors, CXCR4 and CXCR7, have been found in the brain, the role of this chemokine has been expanded from chemoattractant in the immune system to neuromodulatory in the brain. Several pieces of evidence suggest that this chemokine system could crosstalk with the GABAergic system, known to be the main inhibitory neurotransmitter system in the brain. Indeed, GABA and CXCL12 as well as their receptors are colocalized in many cell types including neurons and there are several examples in which these two systems interact. Several mechanisms can be proposed to explain how these systems interact, including receptor–receptor interactions, crosstalk at the level of second messenger cascades, or direct pharmacological interactions, as GABA and GABAB receptor agonists/antagonists have been shown to be allosteric modulators of CXCR4. The interplay between CXCL12/CXCR4-CXCR7 and GABA/GABAA-GABAB receptors systems could have many physiological implications in neurotransmission, cancer and inflammation. In addition, the GABAB agonist baclofen is currently used in medicine to treat spasticity in patients with spinal cord injury, cerebral palsy, traumatic brain injury, multiple sclerosis, and other disorders. More recently it has also been used in the treatment of alcohol dependence and withdrawal. The allosteric effects of this agent on CXCR4 could contribute to these beneficial effects or at the opposite, to its side effects.